Penggunaan Model Contextual Teaching and Learning dalam Peningkatan Hasil Belajar Siswa SMP Kelas VIII Pada Mata Pelajaran Bahasa Indonesia - Ratih Marhaeni Juni Astuti (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Abstract Learning Model is a learning technique that is used by teachers in teaching a particular subject and in the selection of a model must be adjusted in advance with the subject matter. The level of cognitive development of students and the facilities or facilities available in accordance with the learning objectives so that the expected learning model can be achieved. Implementation of learning about the delivery of stories by applying the Contextual Teaching And Learning (CTL) model. CTL is a learning concept that helps teachers relate to students' real-world situations and encourages students to make connections between the knowledge they have and their application in their daily lives. The CTL model runs in accordance with the scenarios in the Learning Implementation Plan (RPP), and has succeeded in creating a conducive learning situation where students are directly involved in the learning process, can also improve student learning outcomes for learning Indonesian which was initially considered boring. The level of students' understanding of the delivery of stories after learning to use the CTL learning model can increase well, this can be seen from the results of the evaluation that in cycle 1, the average score of 67 categories was sufficient and in the second cycle it obtained an average score of 80 with a good category. After being given an action by using the application of the model of conventional teaching and learning (CTL) in cyle 1 students learning completeness is 74% or 20 Students. While in cycle 2 the classical learning achievement to 93% or 25 Students.